Role of fructose in renal cell carcinoma progression - Jixuan Miao; Di Wang; Ruochong Pang; Hao Zhang; Yuyun Wu; Xingwei Sun; Yong Jin (Discover Oncology)
Abstract Renal cell carcinoma (RCC) is a highly malignant tumor with a poor prognosis, underscoring the urgent need for novel therapeutic strategies. RCC cells exhibit rapid proliferation and high metabolic demands, leading to hypoglycemic and hypoxic conditions within the tumor microenvironment (TME). Our study reveals that the fructose transporter Glut5 is prominently expressed in RCC, facilitating increased fructose uptake. This compensatory mechanism supports RCC survival under glucose deprivation and hypoxia. Fructose utilization sustains RCC proliferation, migration, and colony formation in vitro, significantly reduces apoptosis, and accelerates renal cancer growth in vivo. Mechanistically, fructose activates the cAMP/PKA signaling pathway, driving metabolic reprogramming and promoting tumor progression. Furthermore, 2,5-dehydro-D-mannitol (2,5-AM), a competitive inhibitor of fructose transport, significantly inhibits RCC growth both in vivo and in vitro. These findings provide new insights into the role of fructose metabolism in RCC progression and suggest potential therapeutic targets.